Effect of lidocaine on expression of P2X7, p-p38 and IL-Iβ in the thalamus of rats with trigeminal neuralgia. (2nd December 2022) - Liu, Hongmei; Ou, Cehua
ABSTRACT: We investigated whether lidocaine can increase the pain threshold of rats with trigeminal neuralgia by affecting the expression of P2X7, p-p38 and IL-Iβ proteins in the thalamus. Thirty-three male Sprague–Dawley (SD) rats were randomly divided into three groups ( n = 11): Sham group, Ion-CCI (infraorbital nerve chronic constriction injury) group and Ion-CCI+L group(Ion-CCI+lidocaine 10 mg/kg/day, i.p.). The mechanical pain threshold of rats was measured preoperatively and at 1, 3, 5, 7, 9, 11 and 14days after operation with the von Frey filament sensor tester. Fourteen days after operation, the rats were dissected to collect their whole brain, thalamus and trigeminal ganglion to detect IL-1β, P2X7, p38, and p-p38 protein expression. The pain threshold of rats in Ion-CCI+L group was lower than that in Sham group ( p < 0.01) and higher than that in Ion-CCI group ( p < 0.01).ELISA showed that IL-1β in the thalamus and trigeminal ganglion in Ion-CCI+L group were lower than those in ion-CCI group ( p < 0.05) but higher than those in Sham group ( p < 0.05). Western blot showed that the expression levels of P2X7 and p-p38 in the thalamus of rats in Ion-CCI+L group were lower than those in Ion-CCI group ( p < 0.01) and higher than thaose in Sham group ( p < 0.01), while the expression levels of IL-1β in the thalamus in Ion-CCI+L group were lower than those in Ion-CCI group ( p < 0.05) and higher than those in Sham group ( p < 0.01). Immunofluorescence showed that p-p38 in the thalamus in Ion-CCI+L group was lower than that in Ion-CCI group ( p < 0.05) and higher than that in Sham group ( p < 0.05). Lidocaine can reduce the inflammatory response of the central nervous system and increase the pain threshold of trigeminal neuralgia rats by inhibiting p2x7-p38-IL-1β signaling pathway.This pathway play an important role in the pathogenesis of trigeminal neuralgia, and it may be one of the targets for the treatment of trigeminal neuralgia.